2009
DOI: 10.1007/s11355-009-0087-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between soil properties and incidence of pine wilt disease at stand level

Abstract: This study was conducted to evaluate and compare soil properties between pine stands either damaged or undamaged by pine wilt disease in Jinju and Sacheon Cities, which are areas in Korea severely affected by the disease. Soil physical and chemical properties were generally similar between damaged and undamaged pine stands. There was no significant difference in soil factors related to soil nutrient fertility between damaged and undamaged pine stands, although the incidence of pine wilt disease was affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…However, Kim et al. (2010) found that soil fertility was generally higher at undamaged sites than at damaged plots. The differences in these results may be due to the variation of soil properties with the observation period, forest conditions, and vegetation structure of the sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Kim et al. (2010) found that soil fertility was generally higher at undamaged sites than at damaged plots. The differences in these results may be due to the variation of soil properties with the observation period, forest conditions, and vegetation structure of the sites.…”
Section: Discussionmentioning
confidence: 99%
“…2010). The plots were divided into five stand types: ST1 was an uninfected control, while ST2, ST3, ST4, and ST5 had all been infected by PWD and contained 2.67, 4.33, 6.67, and 8.50 Masson pine stumps per 100 m 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C concentration of tree components was generally greater at sites with poor quality compared with trees growing under better environmental conditions because of low tree-component mineral concentrations or differences in carbon allocation (Peri et al 2010), although the inter and intra-specific variation in C concentration is determined by site conditions, stand conditions, and genetic and environmental factors (Bert and Danjon 2006, Zhang et al 2009, Peri et al 2010. Kim et al (2010a) reported that soil nutrient conditions in red pine stands decline after an incident of pine wilt disease. However, the C concentration of the cone and flower and miscellaneous litter was not affected by the damage caused by pine wilt disease.…”
Section: Litterfall C and N Concentrations In The Pine Wilt Disease Smentioning
confidence: 99%
“…and red pine (P. densiflora S. et Z.) are the most dominant and important coniferous tree species that are severely disturbed by PWD throughout Korea (Kim et al 2010, Kwon et al 2011, Jeong et al 2013. Although numerous biomass estimation models have been developed for red pine in Korea , Noh et al 2013, no studies are available to predict tree C and N content in disturbed forest ecosystems such as PWD-disturbed forests.…”
Section: Introductionmentioning
confidence: 99%